2x-5=x-(5x-7)

Simple and best practice solution for 2x-5=x-(5x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5=x-(5x-7) equation:


Simplifying
2x + -5 = x + -1(5x + -7)

Reorder the terms:
-5 + 2x = x + -1(5x + -7)

Reorder the terms:
-5 + 2x = x + -1(-7 + 5x)
-5 + 2x = x + (-7 * -1 + 5x * -1)
-5 + 2x = x + (7 + -5x)

Reorder the terms:
-5 + 2x = 7 + x + -5x

Combine like terms: x + -5x = -4x
-5 + 2x = 7 + -4x

Solving
-5 + 2x = 7 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-5 + 2x + 4x = 7 + -4x + 4x

Combine like terms: 2x + 4x = 6x
-5 + 6x = 7 + -4x + 4x

Combine like terms: -4x + 4x = 0
-5 + 6x = 7 + 0
-5 + 6x = 7

Add '5' to each side of the equation.
-5 + 5 + 6x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 6x = 7 + 5
6x = 7 + 5

Combine like terms: 7 + 5 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 8(5+t)-6(t+2)= | | 4x+10x=10 | | -0.7x-1.75=1.7+0.8x | | 8(-1)-18= | | 2x-5=x-(5-7) | | 1.24*0.2= | | -14u+2u+12u+-u=16 | | -5n-2n=13 | | -5.2q+1.9=-27.8-1.9q | | 3x^7+2x^5-4x^3+6x^2+9=0 | | 15x^2+60x=55 | | -3=(-6)-n | | 2y+1-17=-2y+4 | | 4x-2+3x+2+5x=180 | | 7x+33+8x-18= | | -5y+4= | | 8(2+8n)-7(n-8)=72 | | 9x^2=-36x | | 45=n-54 | | 8b-12=-2 | | 6q-3=15 | | 24p-36=99+9p | | 96=4m | | 2y+1-17=-2-4 | | 5(5-k)-7(7+k)=0 | | 13-(x+6)=5x-5 | | 3.6x=4.2 | | 13u-10u=18 | | 3x-5x+8=8x-2x | | 2x+12+2y=180 | | x-4=0+5x | | 6g-6g+g-1=8 |

Equations solver categories